Gendered Perspectives on Conflict and Violence. - Marcia Texler Segal; Vasilikie Demos (Advances in Gender Research,, 2014)
A global discourse regarding gender and violence is emerging as feminists, media experts, and social scientists consider the place of gender in episodic acts and chronic conditions of violence. The chapters in this two-part volume offer understandings of the relationship between violence and gender from the global to the domestic level. In Part B, authors trace the history of feminist antiviolence efforts, theorize the reproduction of symbolic gender violence, and show how violence might be re-conceptualized in comparative and intersectional perspective. They show how historical, cultural and religious elements contribute to or complicate violence, how development efforts can backfire, and how actions and techniques applied by governments and NGOs can reduce or exacerbate violence. Substantive topics addressed are as varied as masculinity in U.S. prisons, child abuse in Israel, neo-Nazism in Germany and religious nationalism in India. Much of the research was done on the ground through participant observation, interaction in affected communities and interviews with change agents directly involved. Each of the chapters has theoretical as well as policy or social implications.